Effectiveness of a Simulation Curriculum on Clinical Application: A Randomized Educational Trial. Issue 2 (29th April 2022) - Harwayne-Gidansky, Ilana; Askin, Gulce; Fein, Daniel M.; McNamara, Courtney; Duncan, Ellen; Delaney, Kristen; Greenberg, Jacob; Mojica, Michael; Clapper, Timothy; Ching, Kevin
Abstract : Introduction: The use of simulation to develop clinical reasoning and medical decision-making skills for common events is poorly established. Validated head trauma rules help identify children at low risk for clinically important traumatic brain injury and guide the need for neuroimaging. We predicted that interns trained using a high-fidelity, immersive simulation would understand and apply these rules better than those trained using a case-based discussion. Our primary outcomes were to determine the effectiveness of a single targeted intervention on an intern's ability to learn and apply the rules. Methods: This was a prospective randomized controlled trial. Interns were randomized to participate in either a manikin-based simulation or a case discussion. Knowledge and application of the Pediatric Emergency Care Applied Research Network Head Trauma tool were assessed both under testing conditions using standardized vignettes and in clinical encounters. In both settings, interns completed a validated assessment tool to test their knowledge and application of the Pediatric Emergency Care Applied Research Network Head Trauma tool when assessing patients with head injury. Results: Under testing conditions, both being in the simulation group and shorter time from training were independently associated with higher score under testing conditions using standardized vignettes ( P = 0.038 and P < 0.001), but not with clinical encounters. Conclusions: Interns exposed to manikin-based simulation training demonstrated performance competencies that are better than those in the case discussion group under testing conditions using standardized vignettes, but not in real clinical encounters. This study suggests that information delivery and comprehension may be improved through a single targeted simulation-based education.